Crosslinking, Mechanical Properties, and Antimicrobial Activity of Photocurable Diacrylate Urethane/ZnO-Ag Nanocomposite Coating - Truc Vy Do; Minh Nguyet Ha; Tuan Anh Nguyen; Hoang Thu Ha; Thien Vuong Nguyen (Adsorption Science & Technology)
In this article, ZnO-Ag nanohybrids were chemically synthesized in the aqueous medium by reducing silver nitrate with sodium borohydride NaBH4. These nanohybrids were then homogeneously dispersed into the diacrylate urethane/1,6-hexanediol diacrylate resin system at a content of 2 wt%. The structural morphology, mechanical resistances, and crosslinking of the as-prepared nanocomposite coating (nanocoating) were evaluated. The antimicrobial characteristic was tested by keeping track of the lag-log growth phase of E. coli bacteria in the coating existence among cell cultures. The obtained data indicated that the nanohybrids added into the UV curing diacrylate urethane matrices had significantly increased the abrasion resistance, relative hardness, and conversion of the acrylate groups of the nanocoating. In addition, the antibacterial test revealed that the nanocoating had good antibacterial property against E. coli, whereas for the pure coating (without ZnO-Ag nanoparticles), there was no antibacterial activity observed.